Farrow to Finish Swine Operations - Dhuyvetter, Kevin C.; Jones, Rodney D.; Tokach, Mike D. (My University, 1995)
This publication examines the cost and returns for farrow to finish swine production in Kansas.
MF292_1995_10
Keywords: MF292; Livestock; Economics; MF